2023
DOI: 10.1111/njb.03925
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation and soil ecology of threatened Himalayan Trillium habitats in Kashmir Himalaya

Abstract: Understanding the vegetation and soil ecology of natural habitats harbouring threatened species is critical in conservation planning and restoration. The present study investigated the vegetation composition and soil physico‐chemical properties of natural habitats of Trillium govanianum – a threatened Himalayan endemic species. We laid 120 quadrats across eight randomly selected sites where the species was growing in the Kashmir Himalaya. We collected the soil samples from these sites and determined soil physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Magray et al [56] reported that the variation in the IVI of species might be caused by predominant environmental factors. Moreover, the difference in IVI among the sites may be due to the composition of plant species, human activities, and local ecological factors [57].…”
Section: Discussionmentioning
confidence: 99%
“…Magray et al [56] reported that the variation in the IVI of species might be caused by predominant environmental factors. Moreover, the difference in IVI among the sites may be due to the composition of plant species, human activities, and local ecological factors [57].…”
Section: Discussionmentioning
confidence: 99%